INDONESIAN COAL EXPORT TO JAPAN: INTERNATIONAL POLITICAL ECONOMIC REVIEW PERIOD 2010 - 2015 - Ibrahim, Hilmi Rahman; Fadillah, Darul Fikri (Universitas Nasional, 2021)
Indonesia is one of the largest coal-producing countries in the world but is weak in the utilization, technology, and management of coal. Meanwhile, Japan is a developed industrial country with the largest energy consumption in the world, but its resources are limited, so it relies on imports from other countries such as Indonesia. So that there is a coal export-import trade cooperation with the formation of the IJEPA and IJCPD cooperation as bilateral cooperation between Indonesia and Japan which carries the basic concept of the EPA. The purpose of this research is to find out that Indonesian coal exports to Japan can provide benefits for both countries and meet their respective interests. countries viewed in an international political economy review. This research uses the library research method. Japan in fulfilling its energy consumption cannot be separated from trading with other countries such as importing coal from Indonesia which is manifested in the IJCPD Cooperation which is one of the cooperation frameworks in IJEPA, providing great opportunities for Indonesia to maximize management, technology, utilization of coal and bring in investors in Indonesia. . Indonesia and Japan in fulfilling their political economy interests under the auspices of the IJEPA cooperation, in which Japan has established itself as a guarantor country for economic and political stability in the East to Southeast Asia region. Meanwhile, Indonesia had the opportunity to equalize its position and compete with other competing countries that had established cooperation with Japan in the Japanese market.